ESTUDO DOS MEDICAMENTOS UTILIZADOS PELOS IDOSOS ASSISTIDOS PELO PROGRAMA DE ATENÇÃO AO IDOSO (P.A.I.) DA UNIJUÍ - Bueno, Cristiane S.; Oliveira, Karla R. d.; Weber, Débora; Miolo, Giovana M.; Collet, Christiane d. F. (Salão do Conhecimento, 2013)
Resumo